2001
DOI: 10.1007/pl00004057
|View full text |Cite
|
Sign up to set email alerts
|

Steady shock wave reflections in thermochemical nonequilibrium flows

Abstract: The shock wave reflection phenomena in hypersonic steady air flows, including thermochemical nonequilibrium effects, are investigated. The main objectives are to study the influence of these effects on the two shock wave reflections (regular and Mach reflections), on the Mach stem height and on the hysteresis behavior. The air computations are performed using a multi-block MUSCL-TVD finite-volume scheme. The computational results with and without thermochemical effects in the air mixture flow at an upstream Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The interaction of this tangential discontinuity with the reflected shock wave, r 2 ; results in a rarefaction wave, which is seen to interact with the reflected shock wave, r 1 : The existence of the separated flow zone indicates that viscous effects play an important role in the formation of the Type A wave configuration. It should be noted here that the above description of the detailed structure of the Type A wave configuration is based on Burstchell et al's [39] NavierStokes simulations. In Chpoun et al's [37] experiments only the overall wave configurations were recorded.…”
Section: The Hysteresis Process In the Reflection Of Axisymmetric (Comentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction of this tangential discontinuity with the reflected shock wave, r 2 ; results in a rarefaction wave, which is seen to interact with the reflected shock wave, r 1 : The existence of the separated flow zone indicates that viscous effects play an important role in the formation of the Type A wave configuration. It should be noted here that the above description of the detailed structure of the Type A wave configuration is based on Burstchell et al's [39] NavierStokes simulations. In Chpoun et al's [37] experiments only the overall wave configurations were recorded.…”
Section: The Hysteresis Process In the Reflection Of Axisymmetric (Comentioning
confidence: 99%
“…However, in addition, a few secondary hysteresis loops, associated with the interaction between the overall shock wave configuration and the rear edge of the curvilinear cone were obtained. Burstchell et al [39], who simulated the process using a Navier-Stokes code, did succeed in obtaining the Type A wave configuration.…”
Section: Geometrical-variation-induced Hysteresismentioning
confidence: 99%
See 1 more Smart Citation
“…Glaz et al [5] theoretically calculated planar and oblique shock wave reflections for nonequilibrium chemically reacting gases and compared the results with experimental and numerical ones. Grasso and Paoli [6] and Burtschell et al [7] investigated the thermochemical nonequilibrium effects on shock wave reflection phenomena in steady flows. As for viscous effects, Ivanov et al [8] and Khotyanovsky et al [9] numerically studied the steady reflections of strong and weak shock waves to reveal the role of viscosity in the vicinity of the three-shock intersection.…”
mentioning
confidence: 99%
“…With significant thermochemical effects present in the current study, it is important to characterize their anticipated influence upon the MR configuration. Numerous previous studies have confirmed that the overall MR configuration is displaced forward and the Mach stem height is decreased in the presence of nonequilibrium effects [54][55][56][57]. The Mach stem height reduction increases the experimental difficulty as the postshock measurement area is also decreased.…”
Section: B Asymmetric Mach Reflectionmentioning
confidence: 78%